One new species of the genus Dentitegumia Amsel, 1961 (Lepidoptera: Pyralidae: Phycitinae) from Xinjiang, China - Gulzar, Abdukirim; Li, Houhun (Zootaxa, 2026)
One new species, Dentitegumia hamiclaspera Gulzar & Li, sp. nov., is described from Xinjiang, China. Images of the adult and genitalia are provided. The diagnostic characters to distinguish this new species from its allies are also given.